Perancangan Aplikasi Green Media Berbasis Smartphone Sebagai Sarana Media Education dan Entertainment Pada Perguruan Tinggi - Hayat, Abdul; Maesaroh, Siti; Ardiana, Mira (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2019)
The rapid development of technology in the current era where it has entered the era of disruptive 4.0 is felt very necessary for many people to get good information so that it adds insight and education, especially in the scope of Higher Education. No doubt the need for information facilities is a must. However, the background of the previous problems in the absence of a container of student creativity and achievement, resulting in a large number of talents possessed by students cannot be channeled properly, then a lack of appreciation of students regarding news about the achievements of the University. There are 3 Research Methods in this study including observation, and literature review. Then the development through the Green Media application which contains entertainment media content and education is a package that must be packaged properly, effectively and efficiently. With the aim of students being able to access the Green Media application by example listening to radio broadcasts, watching films of student works, and the latest news about Higher Education, besides that the next goal can be used as a place to promote student talent. So that with the existence of this research it is expected that students in Higher Education can find out about the latest achievements and creativity that are currently being achieved by Higher Education today. Keywords: Green Media, Entertainment, dan Education.